PERLINDUNGAN HUKUM TERHADAP ANAK-ANAK DI SUDAN SELATAN ATAS PELANGGARAN HAK ASASI MANUSIA (HAM) BERDASARKAN HUKUM INTERNASIONAL - Yudith Ridzkia; Ian Dharsono Wijaya Pane; Ryan Adiputra; Ade Adhari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Conflict and war is something that cannot be avoided from human life. War is something that cannot be erased or avoided from the history of human life or it can be said that conflict and war will always exist in human life. Today there are many armed conflicts between the state and an opposition group or separatist group within the country. Sudan is a country located on the African continent which has many conflict. The problem of this research begins with the high level of violence against children that makes South Sudan a country with a severe humanitarian crisis due to the conflict that began two years after the country became independent in 2011. Although South Sudan has been bound by several legal frameworks and has agreed to various conventions related to the protection of human rights, but international crimes in this conflict continue to occur and even get worse. This research was conducted by collecting data through a literature review process sourced from books, journals, articles, websites and other valid sources. Then the relevant literature will be examined systematically so that the analytical framework can be developed and analyzed comprehensively on the data obtained regarding the legal protection of children in South Sudan for violations of human rights (HAM) based on international law. The results of this study found that the United Nations (UN) as an international organization that aims to create international security and peace, through UNICEF also states that women and children need to be devoted to handling it, because they are the ones who suffer the most from the effects of war. UNICEF's role is to protect children's human rights, including the right to survival, the right to security, the right to self-development, and the right to participate and express opinions. The involvement of children in armed conflict is a violation of children's rights.